Model Multiple Objective Stochastic Programming for Working Capital Management of Micro, Small and Medium Enterprises in Indonesia - Parapat Gultom; Rina Widyasari; Ismail Husein (Utilitas Mathematica, 2022)
Micro, small, and medium enterprises (MSMEs) play a significant role in Indonesia's economy. However, many of these companies face challenges in effectively managing their working capital due to limited financial knowledge and restricted access to credit from banks. The management of working capital is crucial for the success or failure of a company's business activities. To achieve optimal working capital management, company managers must carefully balance profitability and liquidity. This study aims to develop a working capital management model specifically designed for MSMEs in Surabaya City, taking into account the uncertainty of sales and financial limitations. The research examines the relationship between working capital management and business performance, using primary data collected from MSMEs in Surabaya City through area sampling. The analysis employs multiple linear regression to explore the correlation between profitability and liquidity, represented by variables x1, x2, x3, x4, and x5. Furthermore, a stochastic multi-objective programming approach is utilized to identify an optimal solution considering the uncertain nature of sales. The key variables analyzed include return on assets as a measure of profitability, receivable turnover for liquidity, as well as inventory turnover, accounts payable days, and cash conversion. The findings indicate a positive correlation between accounts payable, inventory turnover, and cash turnover with liquidity. However, both inventory turnover and cash turnover exhibit a negative correlation with profitability.